Evaluating the spillover effects of the Sugira Muryango home-visiting intervention on temperament of children aged (0.3–3years) exposed to domestic violence: A cluster randomized controlled trial - Theodat Siboyintore; Jeanne Marie Ntete; Jean Mutabaruka; Theresa Betancourt; Sarah Jensen; Vincent Sezibera (PLoS ONE, 2025)
Background Domestic violence, intimate partner violence, and violence against children and women adversely affect children’s well-being. The Sugira Muryango Program (SM) in Rwanda, a home-visiting intervention, aimed to to improve caregiving practices and family dynamics, may also have potential indirect effects on children’s temperament. Objectives This study assesses the impact of SM on the temperament of younger children whose families benefited from the intervention, comparing their temperament with those under usual care. Methods This study utilized a spillover effect cohort design, focusing on 247 younger siblings of children enrolled in the Sugira Muryango Program (SM) to assess potential spillover effects of the intervention. The temperament of these siblings was measured using the Infant Behavior Questionnaire–Revised Short Form, which was translated into native language of the respondents. Multiple linear regression analysis was performed using SPSS version 29, with the treatment group (SM vs. UC) as the main predictor and temperament as the dependent variable. Results The analysis showed no statistically significant differences in key temperament traits such as surgency, negative emotionality, and orienting capacity between the intervention and control groups. The findings indicated that changes in surgency (B =  1.984, t =  1.183, p =  0.24), negative emotionality (B =  -1.657, t =  -0.915, p =  0.36), and orienting capacity (B =  0.551, t =  0.313, p =  0.75) were not significant. Conclusion The results suggest that SM had limited spillover effects on the temperament traits of younger siblings. Given that the intervention was primarily designed to improve broader family dynamics rather than directly impact child temperament, these findings highlight the importance of focusing on direct intervention strategies aimed explicitly at the target child population. Future research should align with the theory of change by examining caregiver-related outcomes, such as parenting practices and mental health, which may influence child temperament. Additionally, considering potential external factors like the COVID-19 pandemic may have influenced the effectiveness of the intervention.